IMPULSIVE BUYING PADA DEWASA AWAL DI YOGYAKARTA - Henrietta, Paulus (Faculty of Psychology, Diponegoro University, 2012)
This research aimed to know the impulsive buying tendency of early adult in Yogyakarta. Impulsive buying was a buying activity without cosideration, and accompanied by strong emotional response. High impulsive buying tendency occured between age 18 to 39 years old. This research was a quantitative descriptive research with 395 subjects. Generally, the impulsive buying tendency in this research was low. Based on comparation between man and woman, it was found that woman was more impulsive than man. The result also showed that married person was more impulsive than unmarried person. Based on the types of job, there was several different among those types. But there was no different of impulsive buying tendency based on the education background level.Keywords: impulsive buying, early adult